Prognostic Factors of Long-term Survival among Rheumatic Heart Disease using Standard versus Cox Proportional Hazard Mixture Cure Model - Idham Abu Hasan, Nurhasniza; Azura Md.Ghani, Nor; Asri Mohd Ghani, Khairul; Izan Mohd Ghani, Khairul; Abu Hasan, Nurhasnira (International Journal of Engineering and Technology, 2019)
The mixture cure model brings a great interest among researchers to the analyses survival data in the presence of cured. This study highlighted the importance of cured to be considered when the study population consists of two different type of groups. Â In such situations, the appropriate model is warranted. In this work, the standard Cox Proportional Hazard (PH) model and Cox PH mixture cure model were employed in order to highlight the difference and the usefulness of the mixture cure model over standard model. The Rheumatic Heart Disease (RHD) dataset could be applied for this purpose. Resultsâ€”The cured fraction was estimated to be 93.7%. The cure analysis shows the effect of Coronary Pulmonary Bypass (P-value=0.015), Mitral procedure (P-value=0.067) and Age (P-value=0.035) were significantly associated with cured among the RHD patients. Â Meanwhile, the length of hospital stay (P-value=0.055) and older age (P-value=0.063) were significantly associated with uncured patients. However, the standard Cox PH model do not allow to discriminate the effects of prognostic factors between these two different patients. The results reveled that HPT (P-value<0.030), emergency Intra Operative status (P-value=0.001), Mitral valve procedures (P-value=0.031), CPB (P-value=0.000), HOSP (<6 days groups) (P-value=0.020) and Redo Post-Operative status (P-value=0.002) were identified as factors associated with the time to death among patients. Conclusionâ€” The results exhibited the advantages of mixture cure model over standard survival model when the cured present in the data.Â Â